Preparation method for enhancing wear resistance of copper-carbon composite material through Ti2AlC
By using a wet -type ultrasonic decentralization method in copper carbon composite materials to treat Ti2ALC powder to improve its particle surface area and surface activity, it solves the problem of insufficient decentralization of Ti2ALC powder in the existing technology, which significantly improves the resistance of the material Gratitude and comprehensive mechanical properties.
Patent Information
- Application Number
- CN202411583658.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
AI Technical Summary
The existing MAX phase Ti2AlC powder is not dispersed enough in copper-carbon composite materials, resulting in the failure to further improve the surface area and surface activity, affecting its close bond with the copper-carbon material matrix, and unable to improve the Ti2AlC/Cu-C composite materials. Structural stability and wear resistance.
Wet ultrasonic dispersion method is used to mix Ti2AlC powder with sodium dodecyl sulfate dispersant. After ultrasonic treatment, drying, ball milling, stress relief annealing and discharge plasma sintering are performed to increase the particle surface area and surface activity of Ti2AlC powder, thereby enhancing its Bonding strength with copper carbon materials.
By improving the particle surface area and surface activity of the Ti2ALC powder, the combination of the CU-TI2ALC interface has been significantly improved, and the structural stability and abrasion resistance of the composite material have been enhanced. Mechanical performance.
Smart Images

Figure DFAQ4RY707PCFL3NPYTF82X7OW7BPFYI33ITXKMN 
Figure OJPM2ZNENRQL57LDYIQIXQ4VO10BD7T17DA9M9EJ 
Figure SCFA5GEHHAK4PG3OXBAOA9CMR97VTBDZ1BUGUNWE
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of MAX phase reinforced copper-carbon wear-resistant materials, and specifically relates to a preparation method of a Ti2AlC reinforced copper-carbon composite material with wear resistance. Background Art
[0002] MAX phase reinforced copper-carbon wear-resistant material is a new type of composite material that combines the high wear resistance of MAX phase ceramics with the toughness, thermal conductivity and electrical conductivity of copper-carbon substrates. It is suitable for fields with extreme conditions and high performance requirements. It has a wide range of applications, including turbine blades, bearings and seals in aerospace, cylinder liners, valves and piston rings in the automotive industry, heat dissipation components in electronic and thermal management equipment, pumps, pipes and valves in energy equipment, and industrial tools and molds, etc., which can significantly extend the service life of equipment and reduce maintenance frequency. Due to its special layered structure, it has both the electrical conductivity of metals and the high hardness and wear resistance of ceramics, and is suitable for high temperature and high friction environments. The preparation of composite materials is usually carried out through processes such as powder metallurgy and hot pressing sintering, so that MAX phase particles are evenly distributed in the matrix to improve the overall performance. In order to improve the interface bonding strength, interface treatment or chemical modification is usually used to ensure the stability and anti-shedding ability of the material in a high wear environment. MAX phase materials will also form a self-lubricating oxide film during the friction process, effectively reducing wear.
[0003] Ti2AlC reinforced copper-carbon composite is an advanced composite material. By introducing MAX phase ceramic Ti2AlC into the copper-carbon matrix, it combines the high wear resistance, high temperature resistance and oxidation resistance of Ti2AlC with the high toughness and thermal conductivity of the copper-carbon matrix, and is suitable for applications under extreme conditions. Its preparation process mainly includes powder metallurgy and hot pressing sintering. By finely controlling the temperature, pressure and atmosphere, it ensures that the Ti2AlC particles are evenly distributed in the matrix and form a strong bond with the matrix, thereby improving the structural strength and wear resistance of the material. At the same time, the layered structure of Ti2AlC has a self-lubricating effect and oxidation resistance in friction, which can significantly reduce the performance degradation caused by wear and high-temperature oxidation. Due to its durability and stability, it is in line with the trend of green manufacturing and sustainable development, and is expected to be used in nuclear energy, wind power and chemical equipment in the future to reduce maintenance costs and resource consumption. With the advancement of materials science, Ti2AlC reinforced copper-carbon composites will also be widely used in electronic components, chip heat dissipation and thermal management equipment, providing a strong impetus for the research and development and industrial application of new composite materials. However, the existing method of introducing MAX phase Ti2AlC powder into the copper-carbon wear-resistant material matrix has insufficient particle dispersion, so that the surface area and surface activity of the particles cannot be further improved, thereby affecting its further close bonding with the copper-carbon wear-resistant material matrix, and unable to further improve the structural stability and wear resistance of the Ti2AlC / Cu-C composite material. Summary of the invention
[0004] The present invention aims to further improve the bonding condition of the ceramic phase Ti2AlC in the copper-carbon composite material matrix, and provides a preparation method for improving the wear resistance of the Ti2AlC / Cu-C composite material by enhancing the activity of the Ti2AlC powder particles. The comprehensive mechanical properties and wear resistance of the prepared copper-based wear-resistant material are significantly improved.
[0005] The technical solution of the present invention: A method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance specifically comprises the following steps: (i) wet ultrasonic dispersion: firstly, Ti2AlC powder is added into a beaker containing sodium dodecyl sulfate dispersant and ultrasonically dispersed; (ii) Drying: Place the ultrasonicated beaker in a vacuum drying oven until the solvent is completely evaporated; (iii) Ball milling: Place Cu powder and ultrasonically dispersed Ti2AlC powder into a ball mill for ball milling under argon atmosphere; (iv) stress relief annealing: placing the ball-milled powder in a tube furnace, reducing it under a hydrogen atmosphere, and fully grinding the reduced mixed powder; (V) Spark plasma sintering: The ground powder and copper-plated flake graphite are placed in a powder mixer for mixing under an argon atmosphere. Finally, the evenly mixed powder is placed in a graphite mold for spark plasma sintering to obtain a Ti2AlC / Cu-C composite material.
[0006] Preferably, the Cu powder is high-purity electrolytic Cu powder in the shape of grapes, with a purity of 99.999% and a particle size of 500nm; the Ti2AlC powder is high-purity multi-layer flaky ceramic powder with a particle size of 600-800 mesh; and the copper-plated flake graphite (GR / Cu) has a particle size of 50 mesh.
[0007] Preferably, the added amount of the Ti2AlC powder is 15-25wt% calculated by mass fraction, the added amount of the copper-plated flake graphite is 8wt% calculated by mass fraction, and the balance is Cu powder.
[0008] Preferably, the ultrasonic dispersion time is 45-60 minutes, and the amount of dispersant sodium dodecyl sulfate added to the beaker is determined according to the content of Ti2AlC powder.
[0009] Preferably, the temperature of the vacuum drying oven in step (ii) is 40-60°C.
[0010] Preferably, in the step (iii), the ball milling speed is 300-350 r / min, and the ball milling time is 14-16 h.
[0011] Preferably, the ground powder in the step (iv) is sieved through a 800-1000 mesh sieve, and then canned in an argon atmosphere in a vacuum glove box.
[0012] Preferably, in the step (iv), the amount of hydrogen introduced into the tubular furnace is 250-300 ml / min, the temperature for stress relief annealing is 250-350° C., and the annealing time is 1-3 h.
[0013] Preferably, the graphite mold has an inner diameter of ∅20 mm, an outer diameter of ∅60 mm, and a height of 70 mm.
[0014] Preferably, the spark plasma sintering process is to first increase the temperature from room temperature to 550°C~600°C and keep it for 5~8 minutes, then continue to increase the temperature to 900°C~950°C, keep it for 5-10 min, the heating rate is 80~100°C / min, the pre-compression pressure is 15 MPa, and the pressure is increased to 50 MPa during the second heating process. Finally, after cooling with the furnace, a high-performance Ti2AlC / Cu-C composite material is obtained.
[0015] Beneficial effects of the invention: the preparation method of the invention comprises wet ultrasonic dispersion, drying, ball milling, stress relief annealing and spark plasma sintering. While continuing the high performance of Ti2AlC powder itself, the Ti2AlC powder is subjected to ultrasonic dispersion treatment, so that the Ti2AlC powder can obtain a more uniform dispersion state, increase the particle surface area and surface activity, so that the performance of the Ti2AlC powder in the composite material is further improved, the Cu-Ti2AlC interface is greatly improved, and the interface bonding force is enhanced. The improvement of the surface activity of the Ti2AlC powder particles also promotes the formation of strong covalent bonds between the Ti element and the C element, so that the stability of the microstructure inside the composite material is greatly improved. The increase of the Ti-C bond greatly improves the hardness and wear resistance of the material, and the wear rate is significantly reduced, thereby improving the performance of the copper-carbon wear-resistant material and achieving the characteristics of high wear resistance and excellent comprehensive mechanical properties. The Ti2AlC / Cu-C composite material prepared by the invention has a simple and efficient production process, is conducive to large-scale production, and has broad application prospects due to its excellent overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 SEM image of Cu-8 wt%GR / Cu-20 wt%Ti2AlC composite powder; Figure 2 The SEM image of Cu-8 wt%GR / Cu-20 wt%Ti2AlC composite powder prepared from Ti2AlC powder without ultrasonic dispersion; Figure 3 is the SEM image of Ti2AlC powder after ultrasonic dispersion; Figure 4 SEM image of Ti2AlC powder without ultrasonic dispersion. DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0018] Example 1 (1) The addition amounts of Cu powder, Ti2AlC powder, and copper-plated flake graphite (GR / Cu) were calculated according to mass fraction, where the addition amount of Ti2AlC powder was 0 wt%, the addition amount of copper-plated flake graphite was 8 wt%, and the balance was Cu powder; (2) Add Cu powder and Ti2AlC powder into the ball mill in sequence under argon atmosphere for ball milling at a speed of 300 r / min for 16 h. (3) The ball-milled powder was placed in a tube furnace and subjected to stress relief annealing in a hydrogen atmosphere at a temperature of 250 °C for 1 h. After annealing, the powder was ground and sieved. (4) Add the powder obtained in step (3) and copper-plated flake graphite into a powder mixer under an argon atmosphere for mixing. The mixing time is 10 h and the rotation speed is 50 r / min. (5) The powder obtained in step (4) is loaded into a graphite mold for spark plasma sintering. The spark plasma sintering process is as follows: first, the temperature is raised from room temperature to 500 °C and kept at that temperature for 5 min, then the temperature is further raised to 950 °C and kept at that temperature for 10 min. The heating rate is 80 °C / min, the pre-compression pressure is 15 MPa, and the pressure is raised to 50 MPa during the second heating process. Finally, the Ti2AlC / Cu-C composite material is obtained after cooling in the furnace.
[0019] Example 2 (1) The addition amounts of Cu powder, Ti2AlC powder, and copper-plated flake graphite (GR / Cu) were calculated according to the mass fraction, where the addition amount of Ti2AlC powder was 15 wt%, the addition amount of copper-plated flake graphite was 8 wt%, and the balance was Cu powder; (2) Preparation of dispersion: Ultrasonic dispersion of Ti2AlC powder was prepared according to a mass ratio of powder to solvent of 1:10 and 0.5 wt% of sodium dodecyl sulfate. That is, the dispersion was prepared using deionized water and sodium dodecyl sulfate in a mass ratio of Ti2AlC powder to dispersion of 1:10, wherein the content of sodium dodecyl sulfate was 0.5% of the mass of Ti2AlC powder.
[0020] (3) Add Ti2AlC powder and the dispersion prepared in step (2) into a beaker and place it in an ultrasonic environment for ultrasonic dispersion for 45 min; (4) taking the solution obtained in step (3), placing it in a vacuum drying oven for low-temperature drying until the solvent is completely evaporated, the drying temperature is 60°C, and obtaining ultrasonically dispersed Ti2AlC powder; (5) In an argon atmosphere, Cu powder and the Ti2AlC powder obtained in step (4) were added to a ball mill in sequence for ball milling at a speed of 300 r / min for 16 h. (6) The ball-milled powder is placed in a tube furnace and subjected to stress relief annealing in a hydrogen atmosphere at a temperature of 250 °C for 1 h. After annealing, the powder is ground and sieved. (7) Add the powder obtained in step (6) and copper-plated flake graphite into a powder mixer under an argon atmosphere for mixing for 10 h at a speed of 50 r / min; (8) The powder obtained in step (7) is loaded into a graphite mold for spark plasma sintering. The spark plasma sintering process is as follows: first, the temperature is raised from room temperature to 500 °C and kept at that temperature for 5 min, then the temperature is further raised to 950 °C and kept at that temperature for 10 min. The heating rate is 80 °C / min, the pre-compression pressure is 15 MPa, and the pressure is raised to 50 MPa during the second heating process. Finally, the Ti2AlC / Cu-C composite material is obtained after cooling in the furnace.
[0021] Example 3 (1) The addition amounts of Cu powder, Ti2AlC powder, and copper-plated flake graphite (GR / Cu) were calculated according to mass fraction, where the addition amount of Ti2AlC powder was 20 wt%, the addition amount of copper-plated flake graphite was 8 wt%, and the balance was Cu powder; (2) Preparation of dispersion: Ultrasonic dispersion of Ti2AlC powder was prepared according to a mass ratio of powder to solvent of 1:10 and 0.5 wt% of sodium dodecyl sulfate. That is, the dispersion was prepared using deionized water and sodium dodecyl sulfate in a mass ratio of Ti2AlC powder to dispersion of 1:10, wherein the content of sodium dodecyl sulfate was 0.5% of the mass of Ti2AlC powder.
[0022] (3) Add Ti2AlC powder and the dispersion prepared in step (2) into a beaker and place it in an ultrasonic environment for ultrasonic dispersion for 45 min; (4) taking the solution obtained in step (3), placing it in a vacuum drying oven for low-temperature drying until the solvent is completely evaporated, the drying temperature is 60°C, and obtaining ultrasonically dispersed Ti2AlC powder; (5) In an argon atmosphere, Cu powder and the Ti2AlC powder obtained in step (4) were added to a ball mill in sequence for ball milling at a speed of 300 r / min for 16 h. (6) The ball-milled powder is placed in a tube furnace and subjected to stress relief annealing in a hydrogen atmosphere at a temperature of 250 °C for 1 h. After annealing, the powder is ground and sieved. (7) Add the powder obtained in step (6) and copper-plated flake graphite into a powder mixer under an argon atmosphere for mixing. The mixing time is 10 h and the rotation speed is 50 r / min. (8) The powder obtained in step (7) is loaded into a graphite mold for spark plasma sintering. The spark plasma sintering process is as follows: first, the temperature is raised from room temperature to 500 °C and kept at that temperature for 5 min, then the temperature is further raised to 950 °C and kept at that temperature for 10 min. The heating rate is 80 °C / min, the pre-compression pressure is 15 MPa, and the pressure is raised to 50 MPa during the second heating process. Finally, the Ti2AlC / Cu-C composite material is obtained after cooling in the furnace.
[0023] Example 4 (1) The addition amounts of Cu powder, Ti2AlC powder, and copper-plated flake graphite (GR / Cu) were calculated according to the mass fraction, where the addition amount of Ti2AlC powder was 25 wt%, the addition amount of copper-plated flake graphite was 8 wt%, and the balance was Cu powder; (2) Preparation of dispersion: Ultrasonic dispersion of Ti2AlC powder was prepared according to a mass ratio of powder to solvent of 1:10 and 0.5 wt% of sodium dodecyl sulfate. That is, the dispersion was prepared using deionized water and sodium dodecyl sulfate in a mass ratio of Ti2AlC powder to dispersion of 1:10, wherein the content of sodium dodecyl sulfate was 0.5% of the mass of Ti2AlC powder.
[0024] (3) Add Ti2AlC powder and the dispersion prepared in step (2) into a beaker and place it in an ultrasonic environment for ultrasonic dispersion for 45 min; (4) taking the solution obtained in step (3), placing it in a vacuum drying oven for low-temperature drying until the solvent is completely evaporated, the drying temperature is 60°C, and obtaining ultrasonically dispersed Ti2AlC powder; (5) In an argon atmosphere, Cu powder and the Ti2AlC powder obtained in step (4) were added to a ball mill in sequence for ball milling at a speed of 300 r / min for 16 h. (6) The ball-milled powder is placed in a tube furnace and subjected to stress relief annealing in a hydrogen atmosphere at a temperature of 250 °C for 1 h. After annealing, the powder is ground and sieved. (7) Add the powder obtained in step (6) and copper-plated flake graphite into a powder mixer under an argon atmosphere for mixing. The mixing time is 10 h and the rotation speed is 50 r / min. (8) The powder obtained in step (7) is loaded into a graphite mold for spark plasma sintering. The spark plasma sintering process is as follows: first, the temperature is raised from room temperature to 500 °C and kept at that temperature for 5 min, then the temperature is further raised to 950 °C and kept at that temperature for 10 min. The heating rate is 80 °C / min, the pre-compression pressure is 15 MPa, and the pressure is raised to 50 MPa during the second heating process. Finally, the Ti2AlC / Cu-C composite material is obtained after cooling in the furnace.
[0025] The mechanical properties of the Ti2AlC reinforced copper-carbon composite materials obtained in Examples 1-4 were tested, and the test results are shown in Table 1: Table 1 Mechanical properties and average friction coefficient of Ti2AlC reinforced copper-carbon composite samples in Examples 1-4 It can be seen from Table 1 that the introduction of Ti2AlC significantly improves the mechanical properties of the composite material, and the average friction coefficient is also reduced. When 20 wt% Ti2AlC is added, the compressive strength of the composite material reaches a maximum of 270MPa, and the average friction coefficient is reduced to 0.1607, indicating that the addition of 20 wt% Ti2AlC significantly improves the mechanical properties and friction properties of the Cu-C composite material, making the composite material present excellent overall performance.
[0026] Depend on Figure 1 and Figure 2 By comparison, it can be observed that after ultrasonic dispersion, the Cu-8 wt%GR / Cu-20 wt%Ti2AlC composite powder presents an obvious flaky structure and the components are evenly mixed, while the composite powder without ultrasonic dispersion has the disadvantages of being agglomerated and uneven. Figure 1 This powder structure is beneficial to improving the sintering driving force during spark plasma sintering, and can make the composite material obtained after sintering more compact.
[0027] Depend on Figure 3 and Figure 4 It can be clearly seen from the comparison that the Ti2AlC powder after ultrasonic dispersion has irregular single flakes, a large particle surface area, and higher surface activity, while the Ti2AlC powder without ultrasonic dispersion has disadvantages such as multi-layered, more agglomerated, and low dispersion degree. Figure 3 The properties of the powder after ultrasonic dispersion are conducive to better bonding of Ti2AlC powder with the copper matrix, promoting the formation of strong covalent bonds between Ti-C and improving the mechanical properties and wear resistance of the composite material.
[0028] The invention not only continues the high performance of Ti2AlC powder itself, but also performs ultrasonic dispersion treatment on Ti2AlC powder, so that Ti2AlC powder can obtain a more uniform dispersion state, increase the particle surface area and surface activity, further improve the performance of the composite material, greatly improve the Cu-Ti2AlC interface, enhance the interface bonding force, and the improvement of the surface activity of Ti2AlC powder particles also promotes the formation of strong covalent bonds between Ti element and C element, so that the stability of the microstructure inside the composite material is greatly improved. The increase of Ti-C bonds greatly improves the hardness and wear resistance of the material, significantly reduces the wear rate, improves the performance of the copper-carbon wear-resistant material, and realizes the characteristics of high wear resistance and excellent comprehensive mechanical properties. The Ti2AlC / Cu-C composite material prepared by the invention has a simple and efficient production process, is conducive to large-scale production, and has broad application prospects due to its excellent overall performance.
Claims
1. A method for preparing a Ti2AlC-reinforced copper-carbon composite material with wear resistance, characterized in that: The method comprises the following steps: (i) wet ultrasonic dispersion: firstly, adding Ti2AlC powder into a beaker containing sodium dodecyl sulfate dispersant and performing ultrasonic dispersion; (ii) Drying: Place the ultrasonicated beaker in a vacuum drying oven until the solvent is completely evaporated; (iii) Ball milling: Place Cu powder and ultrasonically dispersed Ti2AlC powder into a ball mill for ball milling under argon atmosphere; (iv) stress relief annealing: placing the ball-milled powder in a tube furnace, reducing it under a hydrogen atmosphere, and fully grinding the reduced mixed powder; (V) Spark plasma sintering: The ground powder and copper-plated flake graphite are placed in a powder mixer for mixing under an argon atmosphere. Finally, the evenly mixed powder is placed in a graphite mold for spark plasma sintering to obtain a Ti2AlC / Cu-C composite material.
2. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The Cu powder is high-purity electrolytic Cu powder in the shape of grapes, with a purity of 99.999% and a particle size of 500nm; the Ti2AlC powder is high-purity multi-layer flaky ceramic powder with a particle size of 600-800 mesh; the copper-plated flake graphite (GR / Cu) has a particle size of 50 mesh.
3. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The addition amount of the Ti2AlC powder is 15-25wt% calculated by mass fraction, the addition amount of the copper-plated flake graphite is 8wt% calculated by mass fraction, and the balance is Cu powder.
4. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The ultrasonic dispersion time is 45-60 minutes, and the amount of dispersant sodium dodecyl sulfate added to the beaker is determined according to the content of Ti2AlC powder.
5. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The temperature of the vacuum drying oven in step (ii) is 40-60°C.
6. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: In the step (iii), the ball milling speed is 300-350 r / min, and the ball milling time is 14-16 h.
7. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The ground powder in the step (iv) is sieved through a 800-1000 mesh sieve, and then canned in an argon atmosphere in a vacuum glove box.
8. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: In the step (iv), the amount of hydrogen introduced into the tubular furnace is 250-300 ml / min, the temperature for stress relief annealing is 250-350°C, and the annealing time is 1-3 h.
9. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The graphite mold has an inner diameter of ∅20 mm, an outer diameter of ∅60 mm, and a height of 70 mm.
10. The method for preparing a Ti2AlC reinforced copper-carbon composite material with wear resistance as claimed in claim 1, characterized in that: The spark plasma sintering process is to first increase the temperature from room temperature to 550°C~600°C and keep it for 5~8 min, then continue to increase the temperature to 900°C~950°C, keep it for 5-10 min, the heating rate is 80~100°C / min, the pre-compression pressure is 15 MPa, and the pressure is increased to 50 MPa during the second heating process. Finally, after cooling with the furnace, a high-performance Ti2AlC / Cu-C composite material is obtained.
Citation Information
Cited By
Method for reinforcing copper-based composite material based on MAX phase
CN119753409A